Integration of Artificial Intelligence in Islamic Education: Transformation of Pedagogy, Curriculum, and Spirituality Based on Maqāṣid al-Sharī‘ah - Siti Afifatun; Firdalina Firdalina; Mulyana Sari; Novalian Kesumasari; Nila Fatmawati; Febridawati Febridawati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2025)
The integration of Artificial Intelligence (AI) in Islamic education brings significant changes to the learning system, pedagogical approach, curriculum development, and spiritual development of students. This study aims to analyze the transformation of Islamic education in the era of artificial intelligence through the perspective of Maqāṣid al-Sharī‘ah. The study uses a qualitative method with a library research approach through a review of various scientific literature, educational theories, and contemporary thinking on AI and Islamic education. The results show three main findings. First, AI makes a positive contribution to the effectiveness, personalization, and accessibility of learning through adaptive learning systems, intelligent tutoring systems, and digital education platforms that can improve the quality of the teaching and learning process. Second, in the dimensions of pedagogy and curriculum, AI encourages the creation of student-centered learning models, improves critical thinking skills and creativity, and demands the reconstruction of the Islamic education curriculum by integrating digital literacy, AI ethics, and Islamic values ​​in a balanced manner. Third, in the spiritual dimension, AI integration should not only be oriented towards technological advancement, but should also strengthen moral awareness, spiritual intelligence, and humanistic values ​​grounded in Islamic teachings. The Maqāṣid al-Sharī‘ah perspective serves as an ethical foundation to ensure that the implementation of AI in Islamic education continues to support the protection of religion, reason, morality, and human well-being. Therefore, the integration of AI in Islamic education needs to be directed towards creating an educational system that balances technological innovation and the strengthening of spirituality.